Implementasi Job Hazard Analysis (JHA) pada Pekerjaan Distribusi Air Minum di PT. XYZ - Mutiarani Mutiarani; Aditya Dwi Putra Fajar; Rahman Hakim; Adi Syahputra Purba (Jurnal Syntax Admiration, 2024)
Drinking water distribution work at PT. XYZ as a supporting part of the construction industry, involves a series of processes that have the potential to be dangerous and have high risks for workers. To ensure worker safety and health, identifying potential hazards and risks is important. The Job Hazard Analysis (JHA) method is an effective solution for carrying out this identification. This study aims to carry out the process of identifying potential hazards and risks and their control in the work of delivering drinking water supplies at PT. XYZ, using the JHA method. This approach allows systematic analysis of each step of the work, so that potential hazards can be clearly identified and the level of risk can be evaluated in depth. The results of the JHA analysis can be used as a basis for formulating effective control strategies to prevent accidents and injuries in the work environment. Based on the study results, the level of risk obtained at each stage of work before implementing controls varies but ranges between H12 or M9. After implementing risk control the residual risk value obtained is reduced to range between L2 to M6. The lowest residual risk value, namely L2, was obtained for the danger of negligence when checking vehicle oil from the previous value of M9 and the highest residual risk value of M6 was obtained for the danger of slippery floors when washing the vehicle from the previous risk value of M9.